Dental erosion: a brief review: una breve revisión - Ccalli Almonte, Yenifer Solanhs (2021)
Dental erosion is the progressive loss of the dental structure associated with acids of non-bacterial origin and with irreversible effects. The consumption of beverages and foods with high acid content corresponds to the main extrinsic factor of dental erosion, while the endogenous acids that project into the mouth through the esophagus during vomiting or regurgitation are part of the intrinsic factors that contribute to this injury. The prevention and treatment of eroded teeth are real challenges in dental practice. Therefore, this article aims to collect information available in the current literature on the etiology, clinical characteristics and treatment of erosive dental wear, to provide a practical guide for dental surgeons and students.